2015
DOI: 10.1016/j.biopsycho.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones and borderline personality disorder features: Preliminary evidence for interactive effects of estradiol and progesterone

Abstract: Cyclical fluctuations in the ovarian hormones 17β-estradiol (E2; estrogen) and progesterone (P4) predict emotions, cognitive processes, and behaviors relevant to Borderline Personality Disorder (BPD); however, there are individual differences in sensitivity to normal hormone shifts. This study examined associations of naturally occurring hormonal changes with concurrent BPD feature expression. Forty women sampled for a flat distribution of the PAI-BOR (n=10 where T<50, n=10 where 50 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 116 publications
1
44
0
Order By: Relevance
“…This has also been demonstrated with regard to risky behaviors in women (e.g., borderline personality disorder symptoms; Eisenlohr-Moul et al, 2015; emotional eating; Klump et al, 2013). Yet, these interactive effects of E2 and P4 have not been evaluated in relation to substance abuse and specifically on drinking in humans.…”
mentioning
confidence: 68%
“…This has also been demonstrated with regard to risky behaviors in women (e.g., borderline personality disorder symptoms; Eisenlohr-Moul et al, 2015; emotional eating; Klump et al, 2013). Yet, these interactive effects of E2 and P4 have not been evaluated in relation to substance abuse and specifically on drinking in humans.…”
mentioning
confidence: 68%
“…Mindfulness skills that increase awareness and acceptance of emotions may help prevent impulsive, aggressive responses to conflicts and stressors, whereas these skills may be less likely to prevent the commission of purposeful acts of violence. Mindfulness-based approaches may also be useful in reducing aggression in disorders characterized by anger rumination, such as borderline personality disorder (Baer & Sauer, 2011; Peters, Geiger, Smart, & Baer, 2014; Eisenlohr-Moul, Girdler, DeWall, & Segerstrom, 2015; Peters et al, under review). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher values of E2 CWP and P4 CWP reflect currently increased levels relative to one's own person means 1 (Singer and Willett, 2003; see Eisenlohr-Moul et al, 2015 for visual depiction of method).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, those with MRMD and histories of abuse show unique alterations in various stress-responsive physiological systems that are not seen in women without a MRMD who have similar abuse histories, including the hypothalamic-pituitary-thyroid axis (Girdler et al, 2004; Bunevicius et al, 2012) and the sympathetic nervous system (Girdler, 2003; Girdler et al, 2007). Finally, we recently found that cyclical increases in P4 were associated with greater susceptibility to mood symptoms and interpersonal problems only among women high in borderline personality features (Eisenlohr-Moul et al., 2015), traits which often develop as adaptations to abuse (Bandelow et al, 2005). …”
Section: Introductionmentioning
confidence: 99%